2017
DOI: 10.1017/s136898001700043x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of eating patterns and snacking in the US Feeding Infants and Toddlers Study 2008

Abstract: Objective: To explore eating patterns and snacking among US infants, toddlers and pre-school children. Design: The Feeding Infants and Toddlers Study (FITS) 2008 was a cross-sectional national survey of children aged 6-47 months, weighted to reflect US age and racial/ethnic distributions. Dietary data were collected using one multiple-pass 24 h recall. Eating occasions were categorized as meals, snacks or other (comprised of all feedings of breast milk and/or infant formula). The percentage of children consumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 21 publications
3
30
1
Order By: Relevance
“…Dessert and snack consumption is particularly problematic in young children because discretionary calories are limited to ∼100–150 kcal/d ( 14 ). In this article, we did not analyze eating occasions and whether these foods are consumed between meals; however, previous FITS showed that 25–28% of total energy intake in early childhood comes from snacks ( 38 ). In addition, other studies in children from 2 to 18 y have shown that both the prevalence of snacking and the amount of energy consumed from snacks have increased considerably over time ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dessert and snack consumption is particularly problematic in young children because discretionary calories are limited to ∼100–150 kcal/d ( 14 ). In this article, we did not analyze eating occasions and whether these foods are consumed between meals; however, previous FITS showed that 25–28% of total energy intake in early childhood comes from snacks ( 38 ). In addition, other studies in children from 2 to 18 y have shown that both the prevalence of snacking and the amount of energy consumed from snacks have increased considerably over time ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…When looking at beverages consumed at various eating occasions, 24–47.9-month-olds were more likely to consume 100% juice and fruit-flavored drinks at every eating occasion compared to 12–23.9-month-olds, but particularly during snack times. This is concerning for while snacks can provide important nutrients [ 28 ], they can also make a significant contribution to overall energy in young children [ 26 , 57 ]. Bleich and Wolfson found that 2–5-year-olds who drink SSBs were more likely to consume salty and sweet snacks, as well as eat more total calories compared to those who do not consume SSBs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed beverage intake among young children across eating occasions [ 24 , 25 ]. Previously, data from the Feeding Infants and Toddlers Study (FITS) demonstrated that consumption of beverages should be monitored as many young children were consuming 100% juice and SSBs at meals, especially at snack times [ 26 , 27 , 28 ]. Although there have been significant shifts in beverage patterns over the past several decades [ 14 , 29 ], no recent studies have focused on the eating occasions at which different types of beverages are consumed by infants and young children.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey carried out by the Infant and Toddler Forum [ 16 ] reported that children as young as age two are being offered large, adult-sized portions of HED snacks. Similarly, in the US, 57% of preschool children are consuming cookies and candy daily [ 17 ]. A study examining US preschoolers aged 2–5 years demonstrated that the frequency of snacking and body weight are positively related [ 18 ].…”
Section: Introductionmentioning
confidence: 99%